Daytime bruxism in individuals undergoing non-elective maxillofacial surgery: a cross-sectional study. - Viana, Débora Ferreira dos Anjos; Sá, Katia Nunes; Brandão da Silveira, Paulo Brasil; dos Santos Pinheiro Barros, Eulália Silva (Journal of Physiotherapy Research / Revista Pesquisa em Fisioterapia, 2025)
INTRODUCTION: A Daytime bruxism is a repetitive and sustained masticatory muscle activity involving tooth contact without the functional purpose of chewing, which can negatively impact the biomechanics of masticatory functions. Studies have pointed to the possible harmful consequences of bruxism, however, in cases of mandibular fractures where early joint movement is essential for functional recovery these effects have not been explored. OBJECTIVE: To identify the frequency of daytime bruxism in individuals undergoing non-elective mandibular surgery and to investigate the possible relation between bruxism, masticatory limitations, and full mouth opening. MATERIALS AND METHODS: The sample consisted of 289 individuals who underwent non-elective maxillofacial surgeries. Oral behavior and mandibular function were assessed using the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD). Pearson's chi-square test was used, with significance set at p ≤ 0.05. RESULTS: Possible daytime bruxism was observed in 203 participants (70.2%); 177 (61.2%) reported being unable to achieve full mouth opening; 94 (32.5%) presented limitations in chewing soft foods, 218 (75.5%) in chewing firm foods, and 232 (80.3%) in chewing hard-consistency foods. CONCLUSION: Awake bruxism was frequent in this population. There was a high prevalence of masticatory dysfunction for hard foods. Limitation in full mouth opening was related to the frequency of bruxism. Further longitudinal studies are needed to confirm these results.